2017
DOI: 10.1108/bij-05-2016-0077
|View full text |Cite
|
Sign up to set email alerts
|

The emergence and evolution of benchmarking: a management fashion perspective

Abstract: Purpose The purpose of this paper is to make a contribution to the benchmarking literature by examining the historical emergence and evolution of benchmarking using the management fashion perspective as a theoretical lens. Design/methodology/approach The research approach followed in this paper can be characterized as explorative and theoretical. Insights from different data sources have been combined to provide a rich description of the emergence and evolution of benchmarking. Findings This analysis casts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 128 publications
(173 reference statements)
1
25
0
Order By: Relevance
“…A full discussion of the history, nature and types of benchmarking is out of the scope of this paper and especially as these have been severally discussed in other publications (e.g. Meybodi, 2015;Madsen et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A full discussion of the history, nature and types of benchmarking is out of the scope of this paper and especially as these have been severally discussed in other publications (e.g. Meybodi, 2015;Madsen et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There can be little doubt that benchmarking is a popular and well-regarded organisational improvement approach that has been well-researched and published in the academic literature. ( Madsen et al 2017;Adebanjo et al 2010;Teuteberg et al, 2013). While some studies (such as Anand and Kodali, 2008;Francis and Holloway, 2007) have identified the importance of adopting a robust benchmarking framework or process, such studies have failed to investigate benchmarking at a granular level.…”
Section: Research Contributionmentioning
confidence: 99%
“…Many scientists made great contributions to the scientific literature on the study of historical aspects and the evolution of benchmarking, creating for it the potential of an advanced management tool (Camp, 1989;Madsen, Slatten, & Johanson, 2017). Methodological aspects of benchmarking, as applied to accounting processes, are discussed in the fundamental work of Beretta, Dossi, and Grove (1998).…”
Section: Research Questionsmentioning
confidence: 99%
“…Management fashions generally start with an understanding away from the scientific approach to management, then become widespread and continue for a certain period and disappear over time following all fashions' nature. It must be admitted that the history of science is the theory cemetery; however, fashionable approaches seem to emerge seasonally and then disappear, very different from scientific theories (Klincewicz, 2017;Madsen et al, 2017;Bondarouk et al, 2019). When it is seen that fashionable approaches that emerged with the aim of rationalization and specialization have no equivalent in the field, their validity is gradually abandoned by making them a subject of discussion in academic circles.…”
Section: Introductionmentioning
confidence: 99%